G. Deleuze: Bodily Mnemonics and Social Desire-Machines - Mickevičius, Arūnas (Problemos, 2008)
The article is devoted to elaborate the meanings of Deleuzean concepts “body without organs” and “desire-machines”, and discuss their interplay. The article sees how these concepts are applied to the analysis of social reality. According to G. Deleuze there are three – nomadic, barbarian despotic or imperial, and capitalistic – social stages. The article deals with the primitive and despotic social stages. The main aim of the article is to justify the thesis that the primitive social organization presupposes and initiates a peculiar bodily mnemonics. And despotic social stage, on the contrary, transforms primitive social organization, denies bodily mnemonics and presupposes new memory of transcendental consciousness.